2019
DOI: 10.1589/jpts.31.850
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combination of therapeutic exercise and psychological intervention for a patient with first-time traumatic shoulder dislocation

Abstract: [Purpose] A young female with first-time traumatic shoulder dislocation showed a good outcome at the 1 year follow-up in returning to work and sports after undergoing a combination of exercise therapy and psychological intervention. [Participant and Methods] A 24-year-old female who worked as an occupational therapist and played badminton for recreation had dislocated her shoulder in a fall. We evaluated her compliance with home-exercise, range of motion, return to work, fear of movement, sports activity level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…9 Movements performed during badminton play can be a therapeutic exercise as a form of psychological intervention. 13 Movements performed during badminton play can be a therapeutic exercise as a form of psychological intervention. The intervention carried out by the author using badminton as a movement therapy for 12 individuals found that badminton movements can reduce the individual's internet addiction.…”
mentioning
confidence: 99%
“…9 Movements performed during badminton play can be a therapeutic exercise as a form of psychological intervention. 13 Movements performed during badminton play can be a therapeutic exercise as a form of psychological intervention. The intervention carried out by the author using badminton as a movement therapy for 12 individuals found that badminton movements can reduce the individual's internet addiction.…”
mentioning
confidence: 99%
“…This study, together with recent studies regarding patient-centered care and psychosocial impart of physical trauma, underline the importance of a more multifactorial approach following surgical treatment, integrating fear-reducing treatment modalities into standard care. 34 , 35 , 37 , 38 Current practice is mainly focused on the physical side of shoulder instability rather than adding the psychosocial impact of physical trauma to this. This study might enable healthcare professionals to quantify the patients’ kinesiophobia and add a new perspective to current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…So, without the complete age makeup of the male and female patient populations, no relationship among gender, age and recurrence could be inferred. 10 , 11 Therefore, it cannot be ruled out that the lower recurrence rate that is seen in the female cohort is not due to the possible older age makeup of the female cohort. Also, with regard to age, there was a wide age range of patients included in this study, ranging from 14 to 69 years of age at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Risk factors for recurrent instability following arthroscopic labral repair include participation in contact sports, age, sex, technical error, number of dislocations prior to surgery, hyperlaxity, and bone loss on the glenoid and/or humeral head. 10 , 11 Multiple studies have reported that male sex is a risk factor of recurrence 8 , 10 ; however, other studies have disputed that claim. 7 , 12 The purpose of this systematic review was to examine the effect that sex has on recurrence of anterior shoulder instability following primary arthroscopic anterior shoulder stabilization.…”
mentioning
confidence: 99%